Paradigma Islam tentang Pengembangan Pendidikan Islam - Bakri, Maskuri (ISLAMICA: Jurnal Studi Keislaman, 2013)
The main purpose of this article is to portray Islam as a paradigm of higher religious education. This paper is a result of a long research initially aimed at finding new perspective on the development of teaching and learning process in Indonesia. The paper finds that the Holy QurâÃ¢n is ample with references on education at all level. It is actually a book of education. The history of Islam has shown that the system, method, and materials of education in the Islamic world are all derived from it. It is this that the paper is interested to discuss. In doing so, it takes into account the conventional distinction between the religious and natural science as far as education is concerned. While the QurâÃ¢n does not make a clear-cut distinction between the two sciences, the difference between the two does serve as a meaningful entryâat least methodologicallyâinto the world of education. The paper goes on to classify some Islamic universities in Indonesia along the line of this distinction. It finds that some of these universities believe in this distinction, while others do not. This belief will in turn shape the way these universities design their vision and carry on their mission.